Glucocorticoid Cotreatment Induces Apoptosis Resistance toward Cancer Therapy in Carcinomas - Herr, Ingrid; Okouoyo, Stella; Krammer, Peter H.; Knebel Doeberitz, Magnus von (Cancer research, 2003)
Chemotherapy and radiation therapy for cancer often have severe side effects that limit their efficacy. Glucocorticoids (GCs) are frequently used as cotreatment because they may have potent proapoptotic properties and reduce nausea, hyperemesis, and acute toxicity on normal tissue. In contrast to the proapoptotic effect of GCs in lymphoid cells, resistance toward cancer therapy-mediated apoptosis was induced in solid tumors of human cervix and lung carcinomas. Filter hybridization, expression data, as well as functional assays identified multiple core apoptosis molecules, which are regulated by GCs in a pro- or antiapoptotic manner. Both antiapoptotic genes such as FLIP and members of the Bcl-2 and IAP family as well as proapoptotic elements of the death receptor and mitochondrial apoptosis pathways were down-regulated in carcinomas resulting in a decreased activity of caspase-8, caspase-9, and caspase-3. In contrast, death receptor and mitochondrial apoptosis signaling as well as caspase activity was enhanced by dexamethasone in lymphoid cells. To restore apoptosis sensitivity in dexamethasone-treated carcinomas, caspase-8 and caspase-9 were transfected. This resensitized tumor cells in vitro and xenografts in vivo to cisplatin induced cell death. These data therefore raise concern about the widespread combined use of GCs with antineoplastic drugs or agents in the clinical management of cancer patients.
Gesehen am 08.04.2021